They will kill you [videorecording (Blu-Ray)] - Rivera, Carlos Rafael, 1970- (Warner Bros. Entertainment Inc., 2026)
"They Will Kill You unleashes a blood-soaked, high-octane horror-action-comedy in which a young woman must survive the night at the Virgil, a demonic cult's mysterious and twisted death trap of a lair, before becoming their next offering in a uniquely brazen battle of epic kills and wickedly dark humor."--